Guardian of the light Denis Hurley : renewing the church, opposing apartheid - Kearney, Paddy (New York : Continuum, 2009)
Denis Hurley was not born in a lighthouse as some people imagine. His father was the keeper of the lighthouse at Cape Point, the guardian of the light that warns the sailors of dangers and guides them away from destruction.  Now the son did not follow in his father's footsteps. But he became a lighthouse keeper too; the guardian of the light that warns of dangers and saves us from destruction. The lighthouse has become a symbol of light and hope and our Archbishop has been doing this work of warning and guiding for the greater part of his [life]. And he has done it with great faithfulness
ARCHBISHOP DENIS HURLEY'S FAMILY TREE; MAP OF SOUTHERN AFRICA; ADVICE TO AN ARCHBISHOP; GUARDIAN OF THE LIGHT; ABBREVIATIONS; PREFACE; ACKNOWLEDGMENTS; PART ONE: "A BOY OF GREAT PROMISE"; PART TWO: PRIEST, BISHOP, ARCHBISHOP; PART THREE: "THE GREATEST EXPERIENCE OF MY WHOLE LIFE"; PART FOUR: PROPHETIC LEADER; PART FIVE: "IN OLD AGE THEY WILL STILL BEAR FRUIT"; Notes; SELECT BIBLIOGRAPHY; INDEX
Includes bibliographical references (p. 356-358) and index.
Description based on print version record.
Keywords: Hurley, Denis E; Catholic Church -- South Africa -- Bishops -- Biography; Religion; RELIGION -- Christianity -- Catholic; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; Hurley, Denis E; Electronic books